SRAGE downregulates the VEGF expression in OHSS ovarian granulosa cells. (2nd September 2021) - Wang, Bijun; Wang, Jingyan; Liu, Yi; Wang, Liang; Du, Mingze; Zhang, Zhan; Guan, Yichun
Abstract: Objective: Ovarian hyperstimulation syndrome (OHSS) is mainly caused by human chorionic gonadotropin (hCG) through vasoactive mediators such as vascular endothelial growth factor (VEGF) and various inflammatory factors. Our previous study showed that soluble receptor for advanced glycation end products (sRAGE) played a protective role in PCOS by inhibiting VEGF, so wanted to explore the role of sRAGE in OHSS. Methods: Two sets of experiments were performed in this study. In part one, sRAGE protein levels in follicular fluid (FF) samples from 60 patients with OHSS and 60 non-OHSS patients were measured by ELISA. In part two, ovarian granulosa cells were isolated from an additional 25 patients with OHSS and cultured. Then, ovarian granulosa cells were treated with different concentrations of sRAGE. Granulosa cells cultured without sRAGE stimulation were used as the control group. The levels of VEGF, amphiregulin (AREG), betacellulin (BTC), and epiregulin (EREG) mRNA were examined by quantitative RT-PCR. The protein levels of VEGF, AREG, BTC, and EREG were measured by ELISA. Results: Compared with non-OHSS patients, patients with OHSS exhibited lower sRAGE levels in both serum and FF ( p  < .05). Treatment with sRAGE decreased the production of VEGF, and the effects were dependent on the concentration of sRAGE ( p  < .05). Simultaneously, the expression of the EGF-like growth factors AREG, BTC and EREG was decreased, and their expression was dependent on the concentration of sRAGE ( p  < .05). Conclusions: sRAGE downregulate VEGF expression in OHSS ovarian granulosa cells, in which EGF-like growth factor pathway may be involved, and sRAGE may play a potential protective role in OHSS.